Efektifitas Pelaksanaan Program PMT (Pemberian Makanan Tambahan) Lokal Terhadap Berat Badan Pada Anak Balita di Desa Krecek Kecamatan Badas Kabupaten Kediri - setyorini, dwi; Laili, Nurul; kartika sari, Melani (STIKES dan AKZI Karya Husada Kediri, 2024)
The nutritional status based on the weight of toddlers in Indonesia is still a health issue. Malnutrition-related problems can lead to underweight in toddlers, hindering their growth and development. This is influenced by socioeconomic status, lack of maternal knowledge about proper toddler feeding. The government has implemented a Supplementary Feeding Program (PMT) using local food to address this nutritional issue, but there is no data on its effectiveness yet. The aim of this research is to assess the effectiveness of the implementation of the PMT program using local food on the weight of toddlers. The study used a comparative descriptive method with a retrospective approach. Sampling was done using total sampling technique with 23 respondents. Data collection technique involved documentation of the PMT program evaluation conducted in March - April 2023. Statistical analysis was done using Paired T Test (<0.05). The research found that before receiving the PMT program, respondents had an average weight of 10.08 kg. After the PMT program, the weight increased to 10.67 kg. The provision of the PMT program using local food effectively increased the weight of toddlers. (P value 0.008 < 0.05). This program can increase calorie intake in toddlers. It is hoped that in the future, parents can independently implement the PMT program to improve the weight of toddlers. Keyword : Nutritional status, Weight, Supplementary feeding program.